2020
DOI: 10.5194/gmd-13-4355-2020
|View full text |Cite
|
Sign up to set email alerts
|

The Community Firn Model (CFM) v1.0

Abstract: Abstract. Models that simulate the evolution of polar firn are important for several applications in glaciology, including converting ice-sheet elevation change measurements to mass change and interpreting climate records in ice cores. We have developed the Community Firn Model (CFM), an open-source, modular model framework designed to simulate numerous physical processes in firn. The modules include firn densification, heat transport, meltwater percolation and refreezing, water isotope diffusion, and firn-air… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 82 publications
(151 reference statements)
0
56
0
Order By: Relevance
“…In addition to IMAU-FDM we also compare SNOWPACK to the NASA Goddard Space Flight Center firn densification model (GSFC-FDMv1) which provides simulated firn properties over the past 40 years for both the Greenland and Antarctic ice sheets (Medley et al, 2020). GSFC-FDM uses the Community Firn Model, a modular, open-source framework for Lagrangian modeling of several firn and firn-air-related processes within a single column (Stevens et al, 2020). The GSFC-FDM simulations are forced by an enhanced-resolution hybridized MERRA-2 that was developed by exploiting a 15-year, 12.5 km resolution offline MERRA-2 reanalysis.…”
Section: Gsfc-fdm Modelmentioning
confidence: 99%
“…In addition to IMAU-FDM we also compare SNOWPACK to the NASA Goddard Space Flight Center firn densification model (GSFC-FDMv1) which provides simulated firn properties over the past 40 years for both the Greenland and Antarctic ice sheets (Medley et al, 2020). GSFC-FDM uses the Community Firn Model, a modular, open-source framework for Lagrangian modeling of several firn and firn-air-related processes within a single column (Stevens et al, 2020). The GSFC-FDM simulations are forced by an enhanced-resolution hybridized MERRA-2 that was developed by exploiting a 15-year, 12.5 km resolution offline MERRA-2 reanalysis.…”
Section: Gsfc-fdm Modelmentioning
confidence: 99%
“…The choice of this value was based on work in Antarctica which found that firn permeability reaches 0 over a range of densities centered on 810 kg m −3 (Gregory et al, 2014). Unfortunately, such studies remain scarce in Greenland, and results do not provide a definite constraint on permeability (e.g., Albert and Shultz, 2002;Sommers et al, 2017). The DTU model uses a similar threshold density to characterize a layer's impermeability but found that 917 kg m −3 gave the best match with observed firn density profiles (Simonsen et al, 2013).…”
Section: Ice Slabsmentioning
confidence: 99%
“…Therefore, changes in elevation of an ice sheet can be modeled using accumulation and temperature data or estimates as inputs to a firn compaction model (FCM). We use accumulation and temperature changes from RACMO2.3p2 outputs and the model developed by Stevens et al (2020) to account for firn compaction [54]. Referring to the implementation by Stevens et al…”
Section: From Modelingmentioning
confidence: 99%